Great Christian jurists in American history - Dreisbach, Daniel L.; Hall, Mark David (Law and Christianity, 2019)
This book profiles nineteen of America's most influential Christian jurists from the early colonial era to the present day. It will be of interest to anyone interested in American legal history and jurisprudence, the role Christianity has played throughout the nation's history, and the relationship between faith and law.